Beyond viral suppression of HIV – the new quality of life frontier. Issue 1 (December 2016) - Lazarus, Jeffrey; Safreed-Harmon, Kelly; Barton, Simon; Costagliola, Dominique; Dedes, Nikos; del Amo Valero, Julia; Gatell, Jose; Baptista-Leite, Ricardo; Mendão, Luís; Porter, Kholoud; Vella, Stefano; Rockstroh, Jürgen
Abstract Background In 2016, the World Health Organization (WHO) adopted a new Global Health Sector Strategy on HIV for 2016–2021. It establishes 15 ambitious targets, including the '90-90-90' target calling on health systems to reduce under-diagnosis of HIV, treat a greater number of those diagnosed, and ensure that those being treated achieve viral suppression. Discussion The WHO strategy calls for person-centered chronic care for people living with HIV (PLHIV), implicitly acknowledging that viral suppression is not the ultimate goal of treatment. However, it stops short of providing an explicit target for health-related quality of life. It thus fails to take into account the needs of PLHIV who have achieved viral suppression but still must contend with other intense challenges such as serious non-communicable diseases, depression, anxiety, financial stress, and experiences of or apprehension about HIV-related discrimination. We propose adding a 'fourth 90' to the testing and treatment target: ensure that 90 % of people with viral load suppression have good health-related quality of life. The new target would expand the continuum-of-services paradigm beyond the existing endpoint of viral suppression. Good health-related quality of life for PLHIV entails attention to two domains: comorbidities and self-perceived quality of life. Conclusions Health systems everywhere need to become more integrated and more people-centered to successfully meet the needs of virally suppressed PLHIV. By doing so, these systems can better meet the needs of all of their constituents – regardless of HIV status – in an era when many populations worldwide are living much longer with multiple comorbidities.